(untitled) (Research, Society and Development, 2022)
This paper aims to analyze the processes through which inclusion has been articulated in settlement schools. The debate is articulated with the following problem: how is inclusion being instituted through public policies in settlement schools? To this end, we conducted literature and documentary research to meet the following specific objectives: a) list the policies of school inclusion that are at the service of the State; b) understand how inclusion policies are being implemented in settlement schools; and c) discuss the complexity in the inclusion process. By presenting the public policies of inclusion, we saw that these discursive practices posed by the policies are constituted as strategies from the foucauldian concept of biopolitics and governmentality, thinking of diversity and difference in the perspective in which the State has been acting through public policies as a way to discipline the subject by correcting their abnormalities.